2016
DOI: 10.2217/bmm-2016-0184
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Identifies N -Acetylmuramoyl- l -Alanine Amidase as a Novel Biomarker of Sepsis

Abstract: This is the first description of N-acetylmuramoyl-l-alanine amidase as a biomarker that can be used alone or in conjunction with other biomarkers to facilitate the diagnosis of sepsis in the critically ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…PGLRYP2 [64] is an enzyme that breaks down glycopeptides and can break down the cell walls of bacteria [65] giving it a principal role in fighting bacterial infection. It is expressed constitutively from hepatocytes [66] and proteomic studies have previously suggested a possible utility in diagnosing sepsis in critically ill patients [67]. Expression can be induced in skin keratinocytes after exposure to certain bacteria [68] as well as in intestinal and oral epithelial cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…PGLRYP2 [64] is an enzyme that breaks down glycopeptides and can break down the cell walls of bacteria [65] giving it a principal role in fighting bacterial infection. It is expressed constitutively from hepatocytes [66] and proteomic studies have previously suggested a possible utility in diagnosing sepsis in critically ill patients [67]. Expression can be induced in skin keratinocytes after exposure to certain bacteria [68] as well as in intestinal and oral epithelial cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inflammatory properties of peptidoglycan were reduced after PG-LYRP-2 degradation (42). Recently, PGLYRP-2 has been described as a candidate biomarker for the diagnosis of critically ill sepsis (43) and the ad-equate immune response against hepatocellular carcinoma (HCC) (44). PG-LYRP-2 also played an important part in the early defense against streptococcus pneumoniae infection (45).…”
Section: Discussionmentioning
confidence: 99%
“…31 N-acetylmuramoyl-L-alanine amidase belongs to a family of hydrolases and proteomic research has suggested that it has a role in differentiating between infectious and non-infectious inflammatory syndromes. 32…”
Section: Proteins With An Increase In Pe Compared With Controlsmentioning
confidence: 99%